UPAYA MEMBENTUK PEMAHAMAN FIQIH WANITA TENTANG HAID PADA MAHASANTRI MA’HAD AL-JAMI’AH DI IAIN - Nur Aisah Rahmah; Santiani Santiani (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Understanding women's fiqh, especially regarding menstruation, is essential in the life of a Muslim woman as it directly relates to worship and daily practices. Accurate comprehension of menstruation fiqh is necessary for a Muslimah to practice Islamic teachings correctly. In Indonesia, Islamic higher education institutions, including Mahad Al-Jamiah at IAIN, play a significant role in shaping women's fiqh understanding among female students, particularly concerning menstruation. This study aims to explore the efforts made by Mahad Al-Jamiah IAIN in developing women's fiqh comprehension on menstruation among female student, as well as to compare approaches implemented in several Mahad Al-Jamiah to assess the effectiveness of the methods used. This research uses a qualitative approach with a literature study method, focusing on the collection and analysis of data from various relevant sources. The results indicate that Mahad Al-Jamiah IAIN Palangka Raya, through its regular Fiqih Nisa studies, has successfully developed students' understanding of menstruation, covering topics such as the rulings on menstruation, postpartum bleeding (nifas), and irregular bleeding (istihadhah). These sessions are conducted intensively to ensure a deep and practical understanding of women's fiqh in everyday life. With this approach, it is expected that the students can perform religious duties according to Islamic law while preserving their dignity and purity.